2015
DOI: 10.1016/j.atherosclerosis.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of cardiovascular disease: Importance of sex and ethnicity

Abstract: Sex differences in incidence and prevalence of and morbidity and mortality from cardiovascular disease are well documented. However, many studies examining the genetic basis for cardiovascular disease fail to consider sex as a variable in the study design, in part, because there is an inherent difficulty in studying the contribution of the sex chromosomes in women due to X chromosome inactivation. This paper will provide general background on the X and Y chromosomes (including gene content, the pseudoautosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 119 publications
1
64
1
4
Order By: Relevance
“…Gender as a risk factor for atherosclerosis has already been widely studied, and it has a strong tendency towards male gender due to genetic, hormonal, and even cultural reasons (Winham, et al, 2015). However, when the relationship between the G894T polymorphism of the eNOS gene between the case and control groups with both male and female genotypes was evaluated in our study, no statistical difference was found.…”
Section: Discussioncontrasting
confidence: 66%
“…Gender as a risk factor for atherosclerosis has already been widely studied, and it has a strong tendency towards male gender due to genetic, hormonal, and even cultural reasons (Winham, et al, 2015). However, when the relationship between the G894T polymorphism of the eNOS gene between the case and control groups with both male and female genotypes was evaluated in our study, no statistical difference was found.…”
Section: Discussioncontrasting
confidence: 66%
“…Several studies have documented the role of SNPs in various genes in the escalating risk of CAD [18, 19]. PON1 is known to play important roles such as an antioxidant, anti-inflammatory, and antiatherosclerotic functions by preventing LDL oxidation [20].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In females, variants in genes on the X chromosome that undergo X inactivation typically show mosaic expression of the phenotype in a particular tissue or system, or may lead to skewed lyonization. [15][16][17][18] As the reproductive organs form, sex steroid hormones differing between males and females will be secreted and influence body size, organ size, tissue composition (lean body mass, body fat), gastric acid secretion, gastric emptying time, circulating proteins that may bind medications, renal function, immune reactivity, and drug metabolizing enzymes; 19 all of which influence absorption, distribution, metabolism, and elimination of drugs. While many of these differences may influence medication efficacy and toxicity can be attributed, in part, to underlying differences in hormone expression, hormonal status and potential interactions of pharmaceuticals with pathways modulated by sex steroids are usually not considered in preclinical studies for drug development, clinical trials, or reporting of ADRs.…”
Section: Physiologic Differencesmentioning
confidence: 99%